Carried away : the invention of modern shopping - Bowlby, Rachel, 1957- (Columbia University Press, 2001)
Asserting that a history of shopping was, until recently, a history of women, Rachel Bowlby trains her eye on the evolution of the modern shopper. She uses a compelling blend of history, literary analysis, and cultural criticism to explore the rise of department stores and supermarkets of the United States, France, and Great Britain. Bowlby recalls the fascinating early days of these institutions. In the mid-nineteenth century, when department stores first developed, their fabulous new buildings brought middle-class women into town, where they could indulge in what was then a new a.